Tetralogy of Fallot with Scimitar syndrome in VACTERL: a very rare association - Anand, Puneet (International Journal of Contemporary Pediatrics, 2017)
The most common congenital cardiac malformation that occurs in VACTERL association is ventricular septal defect. Scimitar syndrome is a very rare congenital anomaly of the heart occurring due to maldevelopment of the lung bud or the pulmonary vascularization during early embryogenesis. The occurrence of Scimitar syndrome in VACTERL and its association with another cardiac congenital anomaly such as Tetralogy of Fallot (TOF) is extremely rare. The association of Tetralogy of Fallot with Scimitar syndrome alters the management strategy. Hereby, a very rare combination of Scimitar syndrome and tetralogy of Fallot in a four-year-old boy with VACTERL is presented, who underwent a successful single-stage surgical correction.